Introduction to the Preeclampsia Symposium - Pacheco-Romero, Jose (2017)
During the past two decades, no major advances have been done on the origins of preeclampsia. We know that hypertensive disorders complicate about 5-10% of all pregnancies(1) –apparently more in Peru(2). Complications related to preeclampsia include preterm birth, maternal morbidity and mortality, and long-term risk of maternal cardiovascular disease and metabolic disease in both mother and child(3). In developing countries, among already known socioeconomic and cultural reasons, variations in management account for comparatively higher morbimortality rates, despite not being often based on current evidence. We have proof that ancient civilizations of China, Egypt and India have recognized and described preeclampsia as well as the bleak maternal and fetal prognosis it portends.